Impact of Empirical Antibiotic Therapy on Infection-Related Parameters in Burn Patients at Abdul Moeloek Regional General Hospital, Bandar Lampung - Puspita, Okta; Meiliana, Made Laksmi (Indonesian Journal of Science and Pharmacy, 2026)
Burn injuries increase the risk of infection due to disruption of the skin barrier. Therefore, empirical antibiotics are commonly administered during the early phase of treatment. However, evidence regarding changes in inflammatory parameters following therapy remains limited. This study aimed to analyze the effect of empirical antibiotic administration on inflammatory parameters in burn patients at Abdul Moeloek Regional General Hospital, Bandar Lampung. This retrospective observational study utilized medical record data from 79 burn patients, predominantly adult males. The parameters analyzed included leukocyte, neutrophil, lymphocyte, and platelet counts following empirical antibiotic therapy. All patients showed improvement in platelet counts (79/79). Improvements were also observed in lymphocytes (47/79), leukocytes (35/79), and neutrophils (30/79). Statistical analysis demonstrated significant associations between empirical antibiotic administration and all inflammatory parameters (p = 0.001). Variability in leukocyte and neutrophil responses may reflect systemic inflammatory processes beyond infection. Empirical antibiotic administration in burn patients, predominantly adult males, resulted in significant improvements in inflammatory parameters, with platelet count as the most consistent indicator. However, interpretation should consider the patients’ overall clinical status.